A brief history and recent advances in ozone induced chemiluminescence detection for the determination of sulfur compounds by gas chromatography. Issue 39 (5th August 2016) - Luong, Jim; Gras, Ronda; Hawryluk, Myron; Shearer, Randall
Abstract : Ozone induced chemiluminescence is one of the most viable detection techniques for the chromatographic determination of ultra-trace sulfur compounds in difficult matrices. Abstract : Ozone induced chemiluminescence is one of the most viable detection techniques for the chromatographic determination of ultra-trace sulfur compounds in difficult matrices. First reported and commercialized in the early 90s, the sulfur chemiluminescence detector has undergone substantial transformation in terms of critical component design, performance, and reliability making it a near ideal detector for sulfur detection especially in sample matrices that become increasingly complex. In this article, the development of the detector for chromatography from its inception is presented. In addition to key applications that have been reported in the literature, recent new techniques developed with the most advanced version of the detector, like the use of the detector for total sulfur analysis without chromatographic separation is also reported.